Dinámicas familiares en tiempo de pandemia por Covid 19 en Cartago - Gómez Gonzales, Kelly (Universidad Antonio Nariño, 2022)
The purpose of this research work is to describe the functioning of family dynamics in couples of parents of a private garden in times of pandemic by Covid 19 in the city of Cartago, which was developed from a qualitative methodology, to through a descriptive scope, for which the development of a semi-structured interview was proposed as an instrument for collecting information.